Pendekatan Pembelajaran Yang Efektif Dalam Bahasa Arab - Fiqrotul Azizah; Binti Afhimmatul Chusna; M Faiz Ahdan Hawari; M Yunus Abu Bakar (Kampus Akademik Publiser, 2026)
Arabic language learning in various educational institutions in Indonesia currently faces significant challenges, including low student interest and the stigma that Arabic is a highly difficult subject to master. This primary issue often stems from the use of conventional methods that focus excessively on rigid formal grammatical memorization, thereby neglecting the functional aspects of language in social interaction. This article aims to identify, examine, and analyze various effective approaches and strategies for teaching Arabic to optimize students' linguistic competence and functional communication skills. The research methodology employed is a descriptive qualitative method through library research and an in-depth analysis of various relevant active learning models and scientific literature. The research findings indicate that the selection of appropriate learning strategies is a crucial factor in determining the success of the educational process. The communicative approach has proven to be the most dominant strategy in building speaking proficiency (maharah kalam) by emphasizing language functions as real communication tools rather than mere structural mastery. Meanwhile, the integration of a contextual approach can enhance active student involvement by linking learning materials with daily experiences, making the language more meaningful, natural, and applicable. Furthermore, innovations through Game-Based Learning and the application of multiple intelligences theories have been found to be highly effective in increasing students' intrinsic motivation and self-confidence. The implications of this study emphasize the importance of transforming the educator's role from a mere knowledge transmitter to a creative and innovative facilitator in designing a stimulative learning environment. Success in modern Arabic language learning requires flexibility in method selection and technology integration to create instructional processes that are dynamic, effective, and relevant to global communication demands.